2010
DOI: 10.1515/sg-2010-0028
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Pollination Methods for Creating Corymbia Hybrids

Abstract: Inter-specific Corymbia hybrids are of increasing interest to plantation forestry, yet there is little knowledge of the most suitable controlled pollination methods for this genus. Inter-specific crosses were made between C. torelliana [CT(maternal parent)] and C. citriodora subsp. variegata (CCV), C. henryi (CH) and C. citriodora subsp. citriodora (CCC) using conventional pollination, one-stop pollination (OSP) and artificially-induced protogyny on yellow buds (AIP Y) pollination methods. Additional treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 20 publications
(28 reference statements)
0
26
0
Order By: Relevance
“…The controlled pollination methods (AIP unpollinated, AIP and three-stop pollination) retained 12 % or less of their capsules, whereas open pollination retained ∼40 %, similar to 6 % capsule retention in E. grandis , 5.6-15.5 % for Corymbia hybrids (Dickinson et al 2010) and 5-19 % for some E. grandis hybrids (Horsley et al 2010), but lower than 21 % capsule retention for E. grandis hybrids (Assis et al 2005), 64 % for Eucalyptus urophylla , 71 % for E. grandis (Horsley et al 2010) and 73 % for E. globulus (Suitor et al 2008) using the three-stop method.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…The controlled pollination methods (AIP unpollinated, AIP and three-stop pollination) retained 12 % or less of their capsules, whereas open pollination retained ∼40 %, similar to 6 % capsule retention in E. grandis , 5.6-15.5 % for Corymbia hybrids (Dickinson et al 2010) and 5-19 % for some E. grandis hybrids (Horsley et al 2010), but lower than 21 % capsule retention for E. grandis hybrids (Assis et al 2005), 64 % for Eucalyptus urophylla , 71 % for E. grandis (Horsley et al 2010) and 73 % for E. globulus (Suitor et al 2008) using the three-stop method.…”
Section: Discussionmentioning
confidence: 69%
“…Horsley et al (2010) suggested that damage to the buds of E. grandis, E. smithii (0.7×0.7 cm) and E. macarthurii during emasculation due to small size of the buds was the cause of reduced seed set. Dickinson et al (2010) also found lower capsule retention following AIP treatments in Corymbia hybrids which have large buds compared with E. argophloia and suggested that lower capsule retention may be due to increased physical damage resulting from the pollination method. The number of seeds per retained capsule from the threestop treatment was similar to open pollination, indicating that this procedure was capable of producing seed if capsules were retained.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations